Prospektywna analiza finansowa i jej znaczenie dla przewidywania i przezwyciężania sytuacji kryzysowych w przedsiębiorstwie - Czerny, Janusz (Prospective financial analysis and its meaning for predicting and overcoming contingencies in a corporate, 2006)
Financial analysis, being one of the elements of the whole accounting system and being influenced by both inside and outside users, is becoming a more and more active tool aiding the process of managing a company. Thanks to the development of retrospective analysis managers acquire a tool providing information essential in diagnosing and preventing crisis. This is especially helpful in a market economy which is charactrised by a high degree of risk. The above problems are the theme of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 60-72